Thrombolytic Refusal Over Telestroke. Issue 3 (June 2021) - Zha, Alicia; Rosero, Adriana; Malazarte, Rene; Bozorgui, Shima; Ankrom, Christy; Zhu, Liang; Joseph, Michele; Trevino, Alyssa; Cossey, Tiffany D.; Savitz, Sean; Wu, Tzu Ching; Jagolino-Cole, Amanda
Abstract : Background: Tissue plasminogen activator (tPA) refusal is 4%–6% for acute ischemic stroke (AIS) in the emergency department. Telestroke (TS) has increased the use of tPA for AIS but is accompanied by barriers in communication that can affect tPA consent. We characterized the incidence of tPA refusal in our TS network and its associated reasons. Methods: Patients with AIS who were offered tPA within 4.5 hours from symptom onset according to American Heart Association guidelines were identified within our Lone Star Stroke Consortium Telestroke Registry from September 2015 to December 2018. We compared baseline characteristics and clinical outcomes between patients who refused tPA and patients who accepted tPA. Results: Among the 1, 242 patients who qualified for tPA and were offered treatment, 8% refused tPA. Female and non-Hispanic Black patients and patients with a prior history of stroke were more likely to decline tPA. Patients who refused tPA presented with a lower NIHSS and were associated with a final diagnosis of stroke mimic (odds ratio [OR] 0.23; 95% confidence interval [CI] 0.15–0.36). Good outcome (90-day modified Rankin Scale 0–2) was the same among patients who received tPA and those who refused (OR 0.80; 95% CI 0.42–1.54). The most common reasons for refusal were rapidly improving and mild/nondisabling symptoms and concern for potential side effects. Conclusion: tPA refusal over TS is comparable to previously reported rates; there was no difference in outcomes among patients who received tPA compared with those who refused. Sex and racial differences associated with an increased tPA refusal warrant further investigation in efforts to achieve equity/parity in tPA decisions.